Solid electrolyte material and battery using the same
By adding Li, Ca, Y, Gd and X elements to the solid electrolyte material and using mechanochemical grinding methods, the problem of low lithium ion conductivity in the prior art is solved, and the charging and discharging characteristics and safety of high-performance batteries are improved.
Patent Information
- Application Number
- CN202080064880.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-09-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-09-18
AI Technical Summary
In the prior art, the lithium-ion conductivity of solid electrolyte materials is low and it is difficult to meet the needs of high-performance batteries.
A solid electrolyte material containing elements Li, Ca, Y, Gd and X, wherein X is at least one element selected from F, Cl, Br and I, is prepared by a mechanochemical grinding method to ensure high lithium ion conductivity of the material.
High lithium ion conductivity is achieved, the charging and discharging characteristics and safety of the battery are improved, and the production of hydrogen sulfide is avoided.
Smart Images

Figure CN114402471B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. Background Art
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte.
[0003] Patent Document 2 discloses a solid electrolyte material represented by the compositional formula Li 6-3z Y z X6 (0 < z < 2, X = Cl or Br).
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-129312
[0007] Patent Document 2: WO 2018 / 025582 Summary of the Invention
[0008] Problems to be Solved by the Invention
[0009] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity.
[0010] Means for Solving the Problems
[0011] The solid electrolyte material of the present disclosure contains Li, Ca, Y, Gd, and X, and X is at least one element selected from F, Cl, Br, and I.
[0012] Effects of the Invention
[0013] The present disclosure provides a solid electrolyte material having high lithium ion conductivity. Brief Description of the Drawings
[0014] Figure 1 A cross-sectional view showing the battery 1000 of the second embodiment.
[0015] Figure 2 A schematic view showing the compression molding die 300 used for evaluating the ionic conductivity of the solid electrolyte material.
[0016] Figure 3 A chart showing a Cole-Cole plot of the impedance measurement results of the solid electrolyte material of Example 1.
[0017] Figure 4 A chart showing the initial discharge characteristics of the battery of Example 1. Detailed Description of the Invention
[0018] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0019] (First embodiment)
[0020] The solid electrolyte material of the first embodiment contains Li, Ca, Y, Gd, and X. X is at least one element selected from the group consisting of F, Cl, Br, and I.
[0021] The solid electrolyte material of the first embodiment has high lithium ion conductivity. Therefore, the solid electrolyte material of the first embodiment can be used to obtain a battery having excellent charge and discharge characteristics. An example of such a battery is an all-solid secondary battery.
[0022] The solid electrolyte material of the first embodiment preferably does not contain sulfur. Even if the solid electrolyte material does not contain sulfur, it will not produce hydrogen sulfide, so it is excellent in safety. Such a solid electrolyte material can be used to obtain a battery with excellent safety. It should be noted that the sulfide solid electrolyte disclosed in Patent Document 1 can produce hydrogen sulfide if exposed to the atmosphere.
[0023] In order to improve the ionic conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may be substantially composed of Li, Ca, Y, Gd and X. Here, "the solid electrolyte material of the first embodiment is substantially composed of Li, Ca, Y, Gd and X" means that the molar ratio of the total amount of Li, Ca, Y, Gd and X to the total amount of all elements constituting the solid electrolyte material of the first embodiment is 90% or more. As an example, the molar ratio may also be 95% or more.
[0024] The solid electrolyte material of the first embodiment may also contain an element that is inevitably mixed in. Examples of such elements are hydrogen, nitrogen, or oxygen. Such elements may be present in the raw material powder of the solid electrolyte material, or in the atmosphere used to manufacture or store the solid electrolyte material.
[0025] X may be at least one element selected from Cl and Br. Such a solid electrolyte material has high lithium ion conductivity.
[0026] The solid electrolyte material of the first embodiment may be a material represented by the following composition formula (1).
[0027] Li 6-2a-3d Ca a (Y 1-b G b ) d Br 6-c Cl c (1)
[0028] Among them, the following mathematical formula is satisfied:
[0029] 0 < a < 3,
[0030] 0 < b < 1,
[0031] 0 < c < 6, and
[0032] 0 < d < 1.5.
[0033] The material represented by the compositional formula (1) has high lithium ion conductivity.
[0034] In order to improve the ionic conductivity of the solid electrolyte material, in the compositional formula (1), the mathematical formula 0.01 ≤ a ≤ 0.3 may also be satisfied, or the mathematical formula 0.05 ≤ a ≤ 0.3 may also be satisfied. In order to further improve the ionic conductivity of the solid electrolyte material, the mathematical formula 0.01 ≤ a ≤ 0.2 or 0.05 ≤ a ≤ 0.2 may also be satisfied. In order to further improve the ionic conductivity of the solid electrolyte material, the mathematical formula 0.01 ≤ a ≤ 0.15 or 0.05 ≤ a ≤ 0.15 may also be satisfied. In order to further improve the ionic conductivity of the solid electrolyte material, the mathematical formula 0.01 ≤ a ≤ 0.1 or 0.05 ≤ a ≤ 0.1 may also be satisfied.
[0035] In order to improve the ionic conductivity of the solid electrolyte material, in the compositional formula (1), the mathematical formula 0.8 ≤ d ≤ 1.2 may also be satisfied. In order to further improve the ionic conductivity of the solid electrolyte material, the mathematical formula 1.1 ≤ d ≤ 1.2 may also be satisfied.
[0036] The solid electrolyte material of the first embodiment may also be crystalline or amorphous.
[0037] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-like, spherical or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a manner having a shape of granules or plates.
[0038] For example, when the shape of the solid electrolyte material of the first embodiment is particulate (e.g., spherical), the solid electrolyte material of the first embodiment may also have a median particle diameter of 0.1 μm to 100 μm. The median particle diameter refers to the particle diameter at which the cumulative packing in the particle size distribution based on volume becomes 50%. The particle size distribution based on volume is measured, for example, by a laser diffraction type measuring device or an image analysis device.
[0039] The solid electrolyte material of the first embodiment may have a median particle size of 0.5 μm to 10 μm. Thus, the first solid electrolyte material has higher ion conductivity. Furthermore, the solid electrolyte material of the first embodiment and other materials such as active materials can be well dispersed.
[0040] The solid electrolyte material of the first embodiment may have a smaller median diameter than the active material. This allows the solid electrolyte material of the first embodiment and the active material to be well dispersed.
[0041] <Method for producing solid electrolyte material>
[0042] The solid electrolyte material of the first embodiment is produced, for example, by the following method.
[0043] Two or more types of halide raw material powders are mixed so as to have a target composition.
[0044] As an example, in the target composition of Li 2.9 Ca 0.05 Y 0.6 G 0.4 In the case of Br2Cl4, LiCl raw material powder, LiBr raw material powder, YCl3 raw material powder, GdCl3 raw material powder and CaBr2 raw material powder (i.e., raw material powders of five halides) are mixed in a molar ratio of LiCl:LiBr:YCl3:GdCl3:CaBr2 of about 1:1.9:0.6:0.4:0.05. In order to offset the composition changes that may occur in the synthesis process, the raw material powders may be mixed in a pre-adjusted molar ratio.
[0045] The raw material powders are mechanochemically reacted with each other in a mixing device such as a planetary ball mill (i.e., using a mechanochemical grinding method) to obtain a reaction product. The reaction product may also be fired in a vacuum or in an inert atmosphere. Alternatively, the mixture of raw material powders may be fired in a vacuum or in an inert atmosphere to obtain a reaction product.
[0046] By these methods, the solid electrolyte material of the first embodiment can be obtained.
[0047] (Second embodiment)
[0048] The second embodiment will be described below. Matters described in the first embodiment may be omitted as appropriate.
[0049] In the second embodiment, an electrochemical device using the solid electrolyte material of the first embodiment will be described. As an example of the electrochemical device of the second embodiment, a battery will be described below.
[0050] The battery of the second embodiment includes a positive electrode, an electrolyte layer and a negative electrode. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment. Since the battery of the second embodiment contains the solid electrolyte material of the first embodiment, it has excellent charge and discharge characteristics.
[0051] The battery according to the second embodiment may be an all-solid-state battery.
[0052] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.
[0053] The battery 1000 includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203.
[0054] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .
[0055] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).
[0056] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .
[0057] The solid electrolyte particles 100 are particles made of the solid electrolyte material of the first embodiment, or particles containing the solid electrolyte material of the first embodiment as a main component.
[0058] The positive electrode 201 contains a material capable of inserting and removing metal ions such as lithium ions. This material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).
[0059] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(NiCoMn)O2, Li(NiCoAl)O2 or LiCoO2.
[0060] The positive electrode active material particles 204 may also have a median particle size of 0.1 μm to 100 μm. When the positive electrode active material particles 204 have a median particle size of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 can be well dispersed in the positive electrode 201. As a result, the charge and discharge characteristics of the battery are improved. When the positive electrode active material particles 204 have a median particle size of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is increased. As a result, the battery can operate at a high output power.
[0061] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be well dispersed.
[0062] From the viewpoint of battery energy density and output, in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 to 0.95.
[0063] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm to 500 μm.
[0064] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also be a solid electrolyte layer.
[0065] The electrolyte layer 202 may be composed only of the solid electrolyte material of the first embodiment. Alternatively, the electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment.
[0066] Examples of solid electrolyte materials different from the solid electrolyte material of the first embodiment include Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6, or LiI, wherein X' is at least one element selected from F, Cl, Br, and I.
[0067] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.
[0068] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. The layer formed by the first solid electrolyte material and the layer formed by the second solid electrolyte material may also be stacked along the stacking direction of the battery 1000.
[0069] The electrolyte layer 202 may have a thickness of 1 μm to 1000 μm. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 1000 μm or less, the battery can operate at a high output.
[0070] The negative electrode 203 contains a material capable of absorbing and releasing metal ions such as lithium ions. This material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).
[0071] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds or tin compounds.
[0072] The negative electrode active material particles 205 may also have a median particle size of 0.1 μm to 100 μm. When the negative electrode active material particles 205 have a median particle size of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 can be well dispersed in the negative electrode 203. As a result, the charge and discharge characteristics of the battery are improved. When the negative electrode active material particles 205 have a median particle size of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is increased. As a result, the battery can operate at a high output power.
[0073] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be well dispersed.
[0074] From the viewpoint of battery energy density and output, in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 to 0.95.
[0075] From the viewpoint of energy density and output, the negative electrode 203 may have a thickness of 10 μm to 500 μm.
[0076] For the purpose of improving ion conductivity, chemical stability, and electrochemical stability, at least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a second solid electrolyte material.
[0077] As described above, the second solid electrolyte material may be a halide solid electrolyte.
[0078] Examples of halide solid electrolytes include Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6 or LiI, wherein X' is at least one element selected from F, Cl, Br and I.
[0079] Other examples of halide solid electrolytes are Li p Me q Y r A compound represented by Z6. Wherein p+m'q+3r=6 and r>0 are satisfied. Me is at least one element selected from metal elements and semi-metal elements other than Li and Y. The value of m' represents the valence of Me. "Semi-metal elements" are B, Si, Ge, As, Sb and Te. "Metal elements" are all elements contained in Groups 1 to 12 of the periodic table (except hydrogen) and all elements contained in Groups 13 to 16 of the periodic table (except B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se). From the viewpoint of the ionic conductivity of the halide solid electrolyte, Me can also be at least one element selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb.
[0080] The second solid electrolyte material may be a sulfide solid electrolyte.
[0081] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4 or Li 10 GeP2S 12 .
[0082] The second solid electrolyte material may be an oxide solid electrolyte.
[0083] Examples of oxide solid electrolytes are:
[0084] (i) NASICON type solid electrolytes such as LiTi2(PO4)3 or its element substitution products,
[0085] (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3,
[0086] (iii)Li 14 ZnGe4O 16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their element substitution products,
[0087] (iv)Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an element substitution body thereof, or
[0088] (v) Li3PO4 or its N-substituted form.
[0089] The second solid electrolyte material may be an organic polymer solid electrolyte.
[0090] Examples of organic polymer solid electrolytes are compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure can contain a large amount of lithium salts, thereby further improving ion conductivity.
[0091] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0092] In order to facilitate the transfer of lithium ions and improve the output characteristics of the battery, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid.
[0093] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0094] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorinated solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorinated solvents are fluoroethylene carbonate, fluoromethyl propionate, fluorobenzene, fluoroethyl methyl carbonate or fluorodimethyl carbonate. One non-aqueous solvent selected from them may also be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected from them may also be used.
[0095] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, 0.5 mol / L to 2 mol / L.
[0096] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte solution can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0097] Examples of cations contained in ionic liquids are:
[0098] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,
[0099] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or
[0100] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.
[0101] An example of an anion contained in an ionic liquid is PF6 - 、BF4 - , SbF 6- - 、AsF6 - 、SO3CF3 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - or C(SO2CF3)3 - .
[0102] The ionic liquid may also contain a lithium salt.
[0103] For the purpose of improving the adhesion between particles, at least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder.
[0104] The example of binder is polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber or carboxymethyl cellulose. Copolymer can also be used as binder. The example of such binder is a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture selected from two or more of the above-mentioned materials can also be used as binder.
[0105] For the purpose of improving electron conductivity, at least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent.
[0106] Examples of conductive additives are:
[0107] (i) Graphites such as natural graphite or artificial graphite,
[0108] (ii) Carbon blacks such as acetylene black or Ketjen black,
[0109] (iii) Conductive fibers such as carbon fibers or metal fibers,
[0110] (iv) fluorinated carbon,
[0111] (v) Metal powders such as aluminum,
[0112] (vi) Conductive whiskers such as zinc oxide or potassium titanate,
[0113] (vii) conductive metal oxides such as titanium oxide, or
[0114] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.
[0115] For cost reduction, the conductive auxiliary agent (i) or (ii) mentioned above may be used.
[0116] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a rectangular shape, a sheet shape, a button shape, a flat shape, or a laminated shape.
[0117] Example
[0118] Hereinafter, the present disclosure will be described in more detail while referring to embodiments.
[0119] 《Example 1》
[0120] (Production of solid electrolyte materials)
[0121] In an argon atmosphere having a dew point below -60°C (hereinafter referred to as "dry argon atmosphere"), LiCl, LiBr, YCl3, GdCl3 and CaBr2 are prepared as raw material powders in a molar ratio of LiCl:LiBr:YCl3:GdCl3:CaBr2 of 1:1.9:0.6:0.4:0.05. These raw material powders are crushed and mixed in a mortar. In this way, a mixed powder is obtained. The mixed powder is ground using a planetary ball mill at 600 rpm for 12 hours. In this way, a powder of the solid electrolyte material of Example 1 is obtained. The solid electrolyte material of Example 1 has a composition of Li 2.9 Ca 0.05 Y0.6 G 0.4 The composition represented by Br2Cl4.
[0122] The Li content per unit weight of the solid electrolyte material of Example 1 is measured by atomic absorption spectrometry. The Ca content, Y content and Gd content of the solid electrolyte material of Example 1 are measured by high-frequency inductively coupled plasma emission spectrometry. Based on the contents of Li, Ca, Y and Gd obtained from these measurement results, the Li:Ca:Y:Gd molar ratio is calculated. As a result, the solid electrolyte material of Example 1 has a Li:Ca:Y:Gd molar ratio of 2.9:0.05:0.6:0.4 in the same manner as the molar ratio of the raw material powder.
[0123] (Evaluation of ionic conductivity)
[0124] Figure 2 Schematic diagram showing a press-forming die 300 used for evaluating the ion conductivity of a solid electrolyte material.
[0125] The press forming die 300 includes a punch upper portion 301, a frame 302, and a punch lower portion 303. The punch upper portion 301 and the punch lower portion 303 are both made of electronically conductive stainless steel. The frame 302 is made of insulating polycarbonate.
[0126] use Figure 2 The press forming die 300 shown in FIG. 1 was used to measure the ionic conductivity of the solid electrolyte material of Example 1 by the following method.
[0127] In a dry atmosphere having a dew point of -30°C or less, the powder of the solid electrolyte material of Example 1 (ie, Figure 2 The solid electrolyte material powder 101 is filled in the press forming die 300. In the press forming die 300, a pressure of 300 MPa is applied to the solid electrolyte material of Example 1 using the punch upper part 301 and the punch lower part 303.
[0128] Under the state of applying pressure, the punch upper part 301 and the punch lower part 303 are connected to a constant potential instrument (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The punch upper part 301 is connected to the working electrode and the potential measurement terminal. The punch lower part 303 is connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material is measured by electrochemical impedance measurement at room temperature.
[0129] Figure 3 It is a graph showing a Cole-Cole diagram of the impedance measurement results.
[0130] exist Figure 3The real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ion conduction. Figure 3 The arrow R shown in SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (2).
[0131] σ=(R SE ×S / t) -1 (2)
[0132] Wherein, σ represents ionic conductivity. S represents the contact area between the solid electrolyte material and the upper portion 301 of the punch ( Figure 2 The cross-sectional area of the hollow part of the frame type 302 is equal to that of the hollow part of the frame type 302). SE represents the resistance value of the solid electrolyte material in the impedance measurement. t represents the thickness of the solid electrolyte material (i.e., Figure 2 , the thickness of the layer formed by the powder 101 of the solid electrolyte material).
[0133] The ionic conductivity of the solid electrolyte material of Example 1 measured at 22°C was 1.10×10 -3 S / cm.
[0134] (Battery production)
[0135] In a dry argon atmosphere, the solid electrolyte material of Example 1 and LiCoO2 were prepared in a volume ratio of 30:70 and mixed in a mortar to obtain a mixture.
[0136] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (100 mg), the above-mentioned mixture (10 mg) and aluminum powder (14.7 mg) were stacked in sequence. A pressure of 300 MPa was applied to the stack to form a solid electrolyte layer and a first electrode. The solid electrolyte layer had a thickness of 500 μm.
[0137] Next, metal In (thickness: 200 μm) was stacked on the solid electrolyte layer, and a pressure of 80 MPa was applied to the stacked body to form a second electrode.
[0138] Next, a current collector made of stainless steel was attached to the first electrode and the second electrode, and a current collecting lead was attached to the current collector.
[0139] Finally, an insulating ferrule was used to block the inside of the insulating tube from the outside atmosphere, thereby hermetically sealing the inside of the tube. In this manner, the battery of Example 1 was obtained.
[0140] (Charge and discharge test)
[0141] Figure 4 This is a graph showing the initial discharge characteristics of the battery of Example 1. The initial charge and discharge characteristics were measured by the following method.
[0142] The battery of Example 1 was placed in a constant temperature chamber at 25°C.
[0143] At 72μA / cm 2 The battery of Example 1 was charged at a current density of 1.5 V until the voltage reached 3.7 V. This current density is equivalent to a 0.05 C rate.
[0144] Next, at 72 μA / cm 2 The battery of Example 1 was discharged at a current density of 1.9 V until the voltage reached 1.9 V.
[0145] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 0.89 mAh.
[0146] 《Examples 2 to 21》
[0147] (Production of solid electrolyte materials)
[0148] In Examples 2 to 19, LiCl, LiBr, YCl3, GdCl3 and CaBr2 are prepared as raw material powders in such a manner that the molar ratio of LiCl:LiBr:YCl3:GdCl3:CaBr2 becomes (c-3d):(6-2a-c):(1-b)d:bd:a.
[0149] In Examples 20 and 21, LiCl, LiBr, YCl3, GdCl3 and CaBr2 are prepared as raw material powders in such a manner that the molar ratio of LiCl:LiBr:YBr3:GdBr3:CaBr2 becomes c:(6-2a-c-3d):(1-b)d:bd:a.
[0150] Except for the above matters, the solid electrolyte materials of Examples 2 to 21 were obtained in the same manner as in Example 1. Table 1 shows the values of a, b, c, and d.
[0151] (Evaluation of ionic conductivity)
[0152] The ion conductivities of the solid electrolyte materials of Examples 2 to 21 were measured in the same manner as in Example 1. Table 1 shows the measurement results.
[0153] (Charge and discharge test)
[0154] Using the solid electrolyte materials of Examples 2 to 21, the same operation as in Example 1 was carried out to obtain batteries of Examples 2 to 21. The batteries of Examples 2 to 21 were charged and discharged in the same manner as in Example 1.
[0155] Comparative Examples 1 to 8
[0156] (Production of solid electrolyte materials)
[0157] In Comparative Example 1, LiCl and YCl 3 were prepared as raw material powders so that the molar ratio of LiCl:YCl 3 became 3:1.
[0158] In Comparative Example 2, LiCl, LiBr, and YCl 3 were prepared as raw material powders so that the molar ratio of LiCl:LiBr:YCl 3 was 1:2:1.
[0159] In Comparative Example 3, LiCl, LiBr, and GdCl 3 were prepared as raw material powders so that the molar ratio of LiCl:LiBr:GdCl 3 was 1:2:1.
[0160] In Comparative Examples 4 and 5, LiCl, LiBr, YCl3 and CaBr2 were prepared as raw material powders in such a manner that the molar ratio of LiCl:LiBr:YCl3:CaBr2 became (c-3d):(6-2a-c):(1-b)d:a.
[0161] In Comparative Examples 6 to 8, LiCl, LiBr, YCl3 and GdCl3 were prepared as raw material powders in such a manner that the molar ratio of LiCl:LiBr:YCl3:GdCl3 became (c-3d):(6-2a-c):(1-b)d:bd.
[0162] Except for the above matters, the solid electrolyte materials of Comparative Examples 1 to 8 were obtained in the same manner as in Example 1. Table 2 shows the values of a, b, c, and d.
[0163] (Evaluation of ionic conductivity)
[0164] The ion conductivities of the solid electrolyte materials of Comparative Examples 1 to 8 were measured in the same manner as in Example 1. Table 2 shows the measurement results.
[0165] [Table 1]
[0166]
[0167] [Table 2]
[0168]
[0169] Investigation
[0170] As shown in Table 1, the solid electrolyte materials of Examples 1 to 21 have a relative humidity of 8×10 -4 S / cm or more high ion conductivity.
[0171] As shown by comparing Examples 2 and 4 to 7 with Comparative Example 7, if the value of a representing the molar fraction of Ca is 0.05 to 0.3, the solid electrolyte material has high ion conductivity. As shown by comparing Examples 2 and 4 to 6 with Example 7, if the value of a is 0.05 to 0.2, the ion conductivity is further increased. As shown by comparing Examples 2, 4 and 5 with Example 6, if the value of a is 0.05 to 0.15, the ion conductivity is further increased. As shown by comparing Examples 2 and 4 with Example 5, if the value of a is 0.05 to 0.1, the ion conductivity is further increased.
[0172] It is considered that the solid electrolyte material has high ion conductivity even if the value of a is less than 0.05. The value of a may be, for example, 0.01 to 0.3.
[0173] As shown in Examples 11 and 14 to 17, when the value of d, which indicates the amount of Li deficiency or excess relative to the stoichiometric ratio, is 0.8 to 1.2, the solid electrolyte material has high ion conductivity. As shown by comparing Examples 16 and 17 with Examples 11, 14 and 15, when the value of d is 1.1 to 1.2, the ion conductivity becomes further higher.
[0174] In all of Examples 1 to 21, the batteries were charged and discharged at room temperature.
[0175] Since the solid electrolyte materials of Examples 1 to 21 do not contain sulfur, they do not generate hydrogen sulfide.
[0176] As described above, the solid electrolyte material of the present disclosure is suitable for providing a battery having high lithium ion conductivity and capable of good charge and discharge.
[0177] Industrial Applicability
[0178] The solid electrolyte material disclosed herein is used, for example, in a battery (eg, an all-solid lithium ion secondary battery).
[0179] Explanation of symbols
[0180] 100 Solid Electrolyte Particles
[0181] 101 Powder of solid electrolyte material
[0182] 201 Positive electrode
[0183] 202 electrolyte layer
[0184] 203 Negative electrode
[0185] 204 Positive electrode active material particles
[0186] 205 Negative electrode active material particles
[0187] 300 Pressurized Forming Die
[0188] 301 Punch upper part
[0189] 302 frame type
[0190] 303 punch lower part
[0191] 1000 Batteries
Claims
1. A solid electrolyte material represented by the following compositional formula (1), Li 6-2a-3d Ca a (Y 1-b Gd b ) d Br 6-c Cl c (1) in, satisfying the following mathematical formula: 0<a<3、 0<b<1、 0 < c < 6, and 0<d<1.5。 2. The solid electrolyte material according to claim 1, which satisfies the mathematical formula: 0.01 ≤ a ≤ 0.
3.
3. The solid electrolyte material according to claim 2, which satisfies the mathematical formula: 0.05 ≤ a ≤ 0.
3.
4. The solid electrolyte material according to claim 2, which satisfies the mathematical formula: 0.01 ≤ a ≤ 0.
2.
5. The solid electrolyte material according to any one of claims 1 to 4, which satisfies the mathematical formula: 0.8 ≤ d ≤ 1.
2.
6. The solid electrolyte material according to claim 5, which satisfies the mathematical formula: 1.1 ≤ d ≤ 1.
2.
7. A battery comprising: a positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, in, wherein at least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A
Lithium-ion-conductive ceramic material, lithium-ion-conductive ceramic sintered body, and lithium battery
US20180269526A1
Solid electrolyte material, and cell
WO2018025582A1